Mathematical Economics Comes to America: Charles S. Peirce's Engagement with Cournot's Recherches sur les Principes Mathematiques de la Theorie des Richesses - James R. Wible; Kevin D. Hoover (Duke University, Center for the History of Political Economy (CHOPE), 2013)
Although Cournot's mathematical economics was generally neglected until the mid- 1870s, he was taken up and carefully studied by the Scientific Club of Cambridge, Massachusetts even before his "discovery" by Walras and Jevons. The episode is reconstructed from fragmentary manuscripts of the pragmatist philosopher Charles S. Peirce, a sophisticated mathematician. Peirce provides a subtle interpretation and anticipates Bertrand's criticisms.
Keywords: 330; Charles S. Peirce; A.C. Cournot; mathematical economics; monopoly; duopoly; oligopoly; perfect competition